EU and biodiversity conservation in tropical countries - Ottavio Janni (Fondazione Eni Enrico Mattei (FEEM), 2000)
The importance of biodiversity conservation as a major environmental issue has come to the forefront in recent years. In particular, biodiversity conservation is a critical issue in tropical developing countries, where biodiversity levels are highest and where the threats to this resource are most severe. This paper looks at the policies that European Union countries have undertaken in order to support biodiversity conservation efforts in tropical developing countries, both in terms of official government policies, and in the work of European NGO's and academic institutions. The paper focuses on in situ conservation efforts. There is no common EU policy, and efforts vary widely from country to country. While governments, NGO's and academic institutions often work together, the efforts undertaken by NGO's and academic institutions are more likely to target biodiversity hotspots, and to involve a grass-roots approach to conservation.
Keywords: N5; N50; 330; Biodiversity conservation; EU policy; Artenvielfalt; EU-Politik; Tropen